2015
DOI: 10.1016/j.ydbio.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The endoderm and myocardium join forces to drive early heart tube assembly

Abstract: Formation of the muscular layer of the heart, the myocardium, involves the medial movement of bilateral progenitor fields; driven primarily by shortening of the endoderm during foregut formation. Using a combination of time-lapse imaging, microsurgical perturbations and computational modeling, we show that the speed of the medial-ward movement of the myocardial progenitors is similar, but not identical to that of the adjacent endoderm. Further, the extracellular matrix microenvironment separating the two germ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…Earlier studies in chick suggested that myocardial cells have little ability to migrate, and that endoderm movement drives their migration (Cui et al, 2009;Varner and Taber, 2012). However, a new study showed that chick myocardial cells instead exhibit active displacement and autonomous ventral movement, and that these changes are independent of the endoderm (Aleksandrova et al, 2015). It is thus possible that the ventral movement of these cells in chick is similar to the myocardial subduction we observed in zebrafish.…”
Section: Myocardial Cells Engage In Subduction During Their Medial MImentioning
confidence: 62%
“…Earlier studies in chick suggested that myocardial cells have little ability to migrate, and that endoderm movement drives their migration (Cui et al, 2009;Varner and Taber, 2012). However, a new study showed that chick myocardial cells instead exhibit active displacement and autonomous ventral movement, and that these changes are independent of the endoderm (Aleksandrova et al, 2015). It is thus possible that the ventral movement of these cells in chick is similar to the myocardial subduction we observed in zebrafish.…”
Section: Myocardial Cells Engage In Subduction During Their Medial MImentioning
confidence: 62%
“…regression of the anterior intestinal portal) ( Fig. 2A) (Aleksandrova et al, 2015a;Varner and Taber, 2012). Time-lapse recordings show that as the myocardial progenitor fields approach the midline, the cells autonomously exert mechanical stresses within the tissue (Aleksandrova et al, 2015a).…”
Section: Tissue-scale Motion During Amniote Organogenesis Heart Formamentioning
confidence: 99%
“…Inevitably, cell fatemapping studies in which only cell motion is tracked cannot reveal large-scale composite tissue motion, much less the actual degree of cell-autonomous motility. This is primarily because conventional cell motion tracking studies do not employ the wide mesoscale vantage point needed to unravel large-scale tissue deformations spanning multiple germ layers (Aleksandrova et al, 2015a), and because standard image processing algorithms do not quantify either cellular versus tissue motion or the overall motion of the tissue environment, i.e. cells plus their filamentous ECM scaffold (Zamir et al, 2005).…”
Section: Tissue-scale Motion Includes Ecm Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations